IMPACT OF A TRAINING ON NURSES’ KNOWLEDGE, ATTITUDES, AND PERFORMANCE TOWARDS APPLYING ISBAR IN NURSING ACTIVITIES AT EMERGENCY AND INTENSIVE CARE DEPARTMENT, HANOI MEDICAL UNIVERSITY HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Introduction: Effective and well-structured communication among nurses is fundamental to providing high-quality care and ensuring patient safety. Implementing a standardized communication framework helps promote clarity, completeness, and consistency in nursing handovers. Objective: This study aimed to assess the impact of training on nurses’ knowledge, attitudes, and performance in applying ISBAR in nursing activities in the Emergency and Intensive Care Department at Hanoi Medical University Hospital. Methods: A prospective, descriptive study design was conducted with 45 staff nurses working in the Emergency and Intensive Care Department. Data were collected using a Knowledge-Attitude assessment questionnaire and an observational checklist. Statistical analysis was carried out using SPSS, applying descriptive statistics, the McNemar test, and the Wilcoxon signed-rank test to compare pre- and post-test results. The participants were between 24 and 45 years of age, with females accounting for 68.9% of the sample. After the ISBAR training, the mean knowledge scores increased significantly across all four items: situation, background, assessment, and recommendations (from 13.3 ± 2.7 to 14.6 ± 2.1, p < 0.05). Nurses’ attitudes toward ISBAR showed a positive shift, but it was not statistically significant. The ISBAR training improved overall communication performance, but its influence was inconsistent across various elements of communication performance. Conclusion: Applying the ISBAR framework during handover improved nurses’ knowledge, attitudes, and communication performance during shift changes.